Students' readiness for e-learning during the COVID-19 pandemic in a South-East Asian university: a Rasch analysis - Donnie, Adams; Chuah, Kee Man; Bambang, Sumintono; Ahmed, Mohamed (Emerald Insight, 2021)
Universities have shifted from face-to-face learning environments to e-learning in response to the COVID-19 pandemic. However, the sudden change to online teaching has raised concerns among lecturers about students' readiness for e-learning. This study investigates students' readiness for e-learning during the COVID-19 pandemic and specifically assesses any significant differences between students' gender, age, ethnicity, level of education, field of study and their readiness for an e-learning environment.